DIETARY CORRECTION IN TREATMENT OF ACUTE INTESTINAL INFECTIONS IN YOUNG CHILDREN - N. Kh. Tkhakushinova; N. G. Soboleva ("Paediatrician" Publishers LLC, 2012)
Acute intestinal infections (AII) are still one of the main challenges in pediatrics because of their high prevalence, polyetiology, high rate of severe and complicated forms, especially in young children. The perfect feeding for infants is breast milk. The child feeding with artificial formulas must be supplied with appropriate balanced feeding, assisting not only in physical and mental development, but also in recovery. The article provides information on dietary correction in treatment of AII with formulas containing probiotics.